RATIONAL DESIGN AND CONVENIENT SYNTHESIS OF TWO NOVEL FERROCENE-BASED SULFONYL DIAMINE PRECURSORS - Arancibia, Rodrigo; Gallardo, Miguel; Roussel, Pascal; Henry, Natacha (Journal of the Chilean Chemical Society, 2023)
In the search of new organometallic precursors, this contribution describes a convenient synthesis to obtained new ferrocene-based sulfonyl diamine derivatives. The [(η5-C5H4SO2NH-CH2-CH2-NH2)Fe(η5-C5H5)] (1) and [(η5-C5H4SO2NH-C6H4-NH2)Fe(η5-C5H5)] (2) compounds were prepared by the reaction between (η5-C5H4SO2Cl)Fe(η5-C5H5) and the respective diamine precursor: ethylenediamine (1) or p-phenylenediamine (2) in good yields (86% for 1; 70% for 2). Both compounds were characterized by conventional spectroscopic techniques (infrared spectroscopy, nuclear magnetic resonance spectroscopy, mass spectrometry and elemental analysis) and cyclic voltammetry. In addition, the molecular structure of 1 was determined by single-crystal X-ray diffraction.